Transplantasi Organ Tubuh dalam Perspektif Al-Qur’an: Analisis Tafsir Tematik (Mawḍū‘ī) dan Maqāṣid al-Syarī‘ah - Simatupang, Muhammad Nouval Hasan; Syahrin Harahap (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the ethical and theological dimensions of organ transplantation from a Qur’anic perspective using a thematic (mawḍū‘ī) tafsir approach combined with a normative–theological framework. As a modern medical intervention, transplantation raises questions about the sanctity of the human body, the duty to preserve life, justice, and the prevention of exploitation. By thematically analyzing six key verses, QS al-Mā’idah [5]:2, 32; al-Isrā’ [17]:70; al-Baqarah [2]:195, 286; and an-Naḥl [16]:97, this research integrates classical and modern tafsir (Ibn Kathīr, al-Jalālayn, al-Marāghī, al-Munīr/Wahbah al-Zuḥailī) with Tafsir Al-Qur’an Tematik (Lajnah Pentashihan Mushaf Al-Qur’an) as a representative of contemporary thematic exegesis, alongside current medical literature and real-world testimonies to construct an Islamic ethical framework for transplantation. The findings show that the Qur’anic principles of ḥifẓ al-nafs (preservation of life), ta‘āwun (collaboration in goodness), karāmah (human dignity), ‘adālah (justice), and ḥayāt ṭayyibah (a good life) provide robust theological support for organ donation and transplantation, provided ethical safeguards are met, namely voluntary, informed consent; fairness and transparency; and strict prohibition of commercialization and exploitation. Patient and family testimonies further demonstrate the urgent clinical necessity and human impact of transplantation. The study concludes that, when aligned with Qur’anic ethics and implemented through just clinical governance, organ transplantation is not only permissible but constitutes a noble contribution to social welfare and illustrates the dynamic applicability of Islamic teachings to contemporary biomedical challenges.